Evolution of Defective State of Aluminum Oxide Irradiated with Chromium Ions after Annealing in Oxygen Environment; IOP Conference Series: Materials Science and Engineering; Vol. 168 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2016) - Kabyshev A. V. Alexander Vasilievich (Physical and chemical phenomena in inorganic materials in radiation, electrical and thermal fields, 2017)
Title screen